USING DRONES FOR LANDFILL MONITORING AND PROJECTION CALCULATION - Yackob Astor; Aditia Febriansya; Retno Utami; Muhammad Rizki Firdaus; Farhan Arradzumar Gustaman; Saepul Fariz (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2022)
ABSTRACT: Until now, monitoring the landfill volume in the Sarimukti landfills is calculated by the ratio of trucks converted from tonnage to volume based on the density of the landfill. The various truck specifications and the landfill density conversion process affect the tonnage value. This has an impact on the accuracy of the landfill volume calculation results. This research uses drones as the main tool for monitoring Sarimukti landfills by making a 3D map of the landfill in 2021 as a reference for calculating the volume of existing landfill. The analysis was carried out by comparing the existing landfill volume with the projected landfill volume in 2025 according to the operational period of the landfills. The results of the analysis show that the Sarimukti landfills can no longer accommodate landfill by 2023.Keywords: Drone, Landfill, Contour